Intravenous Immunoglobulin Mediates an Increase in Anti-Platelet Antibody Clearance via the FcRn Receptor - Hansen, Ryan J.; Balthasar, Joseph P. (Thrombosis and Haemostasis, 2002)
We have recently shown that intravenous immunoglobulin (IVIG) therapy leads to an increased rate of anti-platelet antibody clearance in an animal model of immune thrombocytopenia. The present study was performed to confirm the importance of the FcRn receptor in mediating this effect of IVIG. The pharmacokinetics of an anti-platelet antibody, 7E3, were studied in mice lacking expression of FcRn and in control mice, both in the presence and absence of IVIG. IVIG increased the clearance of 7E3 in mice with functioning FcRn receptors, with an average clearance value of 14.4 ± 1.4 ml/d/kg in IVIG treated mice vs. 5.2 ± 0.3 ml/d/kg in controls (P <0.001). In mice lacking expression of FcRn, IVIG treatment did not increase 7E3 clearance (61.0 ± 3.6 ml/d/kg vs. 71.5 ± 4.0 ml/d/kg in controls). Thus, these data support the hypothesis that IVIG increases antibody elimination via saturation of FcRn.
Keywords: Intravenous immunoglobulin; immune thrombocytopenia; pharmacokinetics; FcRn